Market smart : the best in age and lifestyle-specific design. - Acuff, Daniel, ....-; Bonner, David, ....-; Gilmarten, Jim, ....- (New York : Collins design, 2009)
More than 500 age, gender, and lifestyle specific designs from around the world. Learn how top designers target the tastes and trends of their clients to market their products specifically for them. Sorted by consumer groups with the most purchasing power, Market Smart reveals how to target kids, parents, tweens and teens, sports enthusiasts, Generations X & Y, foodies, and baby boomers by exploring all elements of marketing design from print and multimedia advertisements to catch phrases, mascots, logos, product packaging, retail environments, and promotions.Most graphic design books focus on what designers are creating - logos, brochures, product packaging, etc. Market Smart has a fresh perspective by focusing instead on who they are creating for. Effective age, gender, and lifestyle specific designs from around the world are featured. Readers learn how designers use the tastes, trends, and backgrounds of consumers to market their products specifically for them.Chapters are divided by both demographics and psychographics. Demographic chapters include introductions by successful designers, marketers, and industry leaders. A complete index is also included.